Can Dizziness Be Related to Insomnia Severity and Sleep Quality in Young Adults? - Özlem Konukseven; Yeter Saçlı; Ayşenur Küçük Ceyhan (Turkish Archives of Otorhinolaryngology)
Objective: Despite the many medical problems arising from sleep disturbances, few studies have been conducted on vestibular disorders. In this study, we aimed to investigate the relationship between dizziness, sleep quality, severity of insomnia and duration of sleep, in young adults with dizziness. Methods: Forty-nine individuals aged 20-40 years, with normal hearing and complaints of dizziness with an unknown origin were included. The Pittsburgh Sleep Quality Index (PSQI), the Insomnia Severity Index (ISI), and the Dizziness Handicap Inventory (DHI) were used. Results: There was a very strong positive correlation between the PSQI and the ISI (r=0.838, p<0.001). Strong positive correlations were observed between PSQI and the total DHI scores (r=0.660, p<0.001), as well as between ISI and DHI scores (r=0.673, p<0.001). In addition, both PSQI and ISI showed strong positive correlations with the physical subscale of the DHI (r=0.673 and r=0.662, respectively; p<0.001 for both). A significant positive correlation was also found between the daytime dysfunction component of the PSQI and the total DHI score (r=0.640, p<0.001). Moreover, sleep duration was moderately and negatively correlated with the emotional subscale of the DHI (r=-0.454, p=0.001), indicating that shorter sleep duration was associated with greater emotional impairment related to dizziness. Conclusion: Our study showed a high correlation between sleep quality, insomnia severity and dizziness in young adults with dizziness. With inventory, clinicians can contribute to improving people’s quality of life by detecting dizziness associated with sleep disorders.